Prevalence of low test scores in a pediatric psychiatric inpatient population: Applying multivariate base rate analyses. Issue 2 (3rd April 2019) - Gaudet, Charles E.; Cook, Nathan E.; Kavanaugh, Brian C.; Studeny, Jane; Holler, Karen
ABSTRACT: The understanding of neuropsychological functioning in pediatric psychiatric inpatient populations is growing, but limited, resulting in interpretive challenges. This study examined the application of multivariate base rate (MVBR) analysis in a clinical sample to appraise its utility in characterizing the frequency of low scores, as well as predictors of low scores, when using a flexible test battery. Participants included 99 children from a psychiatric inpatient unit referred for neuropsychological testing. Children hospitalized with psychiatric disorders exhibited high rates of low scores at varying criteria across the battery of tests. Hierarchical multiple regression analyses revealed that after accounting for demographic and psychiatric factors, intellectual functioning accounted for approximately 26% of the variance in observed low scores. The results suggest that a substantial percentage of this population produces low scores on neuropsychological testing and, consistent with prior research, intellectual functioning is strongly associated with low score frequency. To our knowledge, this is the first study to examine the clinical application of MVBR analysis in a pediatric psychiatric inpatient population using a flexible test battery. Taken together, this investigation highlights the potential clinical utility of MVBR analysis when interpreting neuropsychological performance in clinical pediatric populations.